Determining the potential locations for industrial estate development using remote sensing and GIS techniques : a case study of Ho Chi Minch city, Vietnam - Lam Dao Nguyen; Kaew Nualchawee; Delsol, Jean-Pierre; Tewari, Vinod K.; The Government of Switzerland (Bangkok : Asian Institute of Technology, 1996)
The preservation of land resources is a major component of the land management process but just as important is the selection of sites for development. An important objective of land planning is to keep environmental disruption to a minimum. This study focuses on remote sensing and GIS techniques specifically for land use planning in industrial estate development. Nowadays, Ho Chi Minh city of Vietnam has been growing rapidly. Therefore, land use changes have been occurring day by day. The total of nine industrial estates in the study area had been approved by the government to develop in the period of 1995-2010 for meeting the need of economical development. The high resolution satellite images are evaluated for their use to upgrade a landuse/ land-cover data base of the study area. GIS analysis function is very useful for land use planning in this study. The spatial analysis will identify areas suitable for the potential industrial estates and the tabular analysis will provide alternatives on the basis of weighting importance of each factor. The results of this study showed that the locations of six proposed industrial estates that will be developed in the initial phase of 1995-2000 should be reconsidered and moved to other places which are more suitable in terms of natural, environmental, socio-economic conditions.
Thesis (M. Eng.) - Asian Institute of Technology, 1996
A thesis submitted m partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Keywords: Geographic information systems; Industrial districts -- Remote sensing; Remote sensing -- Vietnam -- Ho Chi Minh